Maize Mu transposons are targeted to the 5' untranslated region of the gl8 gene and sequences flanking Mu target-site duplications exhibit nonrandom nucleotide composition throughout the genome. - Dietrich, Charles R (2002)
The widespread use of the maize Mutator (Mu) system to generate mutants exploits the preference of Mu transposons to insert into genic regions. However, little is known about the specificity of Mu insertions within genes. Analysis of 79 independently isolated Mu-induced alleles at the gl8 locus established that at least 75 contain Mu insertions. Analysis of the terminal inverted repeats (TIRs) of the inserted transposons defined three new Mu transposons: Mu10, Mu 11, and Mu12. A large percentage (>80%) of the insertions are located in the 5' untranslated region (UTR) of the gl8 gene. Ten positions within the 5' UTR experienced multiple independent Mu insertions. Analyses of the nucleotide composition of the 9-bp TSD and the sequences directly flanking the TSD reveals that the nucleotide composition of Mu insertion sites differs dramatically from that of random DNA. In particular, the frequencies at which C's and G's are observed at positions -2 and +2 (relative to the TSD) are substantially higher than expected. Insertion sites of 315 RescueMu insertions displayed the same nonrandom nucleotide composition observed for the gl8-Mu alleles. Hence, this study provides strong evidence for the involvement of sequences flanking the TSD in Mu insertion-site selection.